The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1080/13562517.2018.1563061
|View full text |Cite
|
Sign up to set email alerts
|

University as a workplace: searching for meaningful work

Abstract: Work in academia is changing, and research suggests that not all the changes are desirable.Higher education is developing in a direction heavily criticised, especially in relation to the concepts of neoliberal and academic capitalism. In this article, we explore meaningful work in a university context. Our focus lies on individual lecturers' positive opportunities to make work meaningful and the university a better place to work for both students and faculty. We examine meaningful work as a relational phenomen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…A mixed-methods study of a large Finnish multidisciplinary research university found contributing factors to meaningful work in the university context included sharing knowledge, collegial viewpoints, and learning (Riivari et al, 2020). However, there are workload and workplace tensions in the university context, impacting scholarly success and well-being.…”
Section: Meaningmentioning
confidence: 99%
“…A mixed-methods study of a large Finnish multidisciplinary research university found contributing factors to meaningful work in the university context included sharing knowledge, collegial viewpoints, and learning (Riivari et al, 2020). However, there are workload and workplace tensions in the university context, impacting scholarly success and well-being.…”
Section: Meaningmentioning
confidence: 99%
“…In this context, organizations enhance the requirement of employees’ proactive behavior. Managers expect employees to break the work limits, and independently identify, analyze, and solve problems, to help organizations resist external risks and maintain a competitive advantage ( Riivari et al, 2020 ; Xu et al, 2021 ). Promoting proactive employee behavior emerges as a key solution to navigating the uncertainties and rapidly changing demands of modern work environments, enhancing job satisfaction and mitigating negative outcomes ( ALGaraawi and Rashid, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this vein, organizations enhance the requirement of employees’ proactive behavior. Managers expect employees to break the work limits, and independently identify, analyze, and solve problems, to help organizations resist external risks and maintain a competitive advantage ( Riivari et al, 2020 ). However, with the economic development of society and changes in work methods, the traditional authoritative style of leadership can no longer adapt to the psychological characteristics of new generation employees, who use new work concepts, techniques, and social rules ( Fang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%